La Pologne, d'autres pays d'Europe centrale et l'Union européenne. Une période d'adaptation et de transition - Puślecki, Zdzislaw (Études internationales, 1995)
In the early nineties, parallel to the increasing integration processes of the European Union, realized through the formation of a uniform common internal market and the conclusion of the treaty of Maastricht of the formation of the European Union, systemic reforms were also taking place in Poland and the other countries of Middle-East Europe. Their substance was transformation of the economies - which up to the present were guided centrally - into market economies. At the same time Poland and the other countries of Middle-East Europe made efforts to come into closer economic cooperation with European Union. An important role in speeding up the economic growth of Poland and the other countries of Middle-East Europe, besides internal financial means, play such sources as external financing, in the form of profitable credits, and also the opening of ready markets.